2021
DOI: 10.1055/a-1324-2763
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of colonoscopy in a colorectal cancer screening program with fecal immunochemical testing: a population-based observational study

Abstract: Background and study aims The aim of this study was to assess adverse events (AEs) associated with colonoscopy in the French colorectal cancer screening program with fecal occult blood test (FOBT). Patients and methods A retrospective cohort study was performed of all colonoscopies performed from 2015 to 2018 for a positive fecal immunochemical test (FIT) in patients aged 50 to 74 years within the screening program in progress in Alsace, part of the French program. AEs were recorded through prospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The adverse events (AEs) from treatments have not been analyzed. We reported elsewhere the AEs of colonoscopies performed in our CRC screening program with FIT 25 . In any case, the higher morbidity and mortality of surgery over endoscopy is well demonstrated 10 11 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The adverse events (AEs) from treatments have not been analyzed. We reported elsewhere the AEs of colonoscopies performed in our CRC screening program with FIT 25 . In any case, the higher morbidity and mortality of surgery over endoscopy is well demonstrated 10 11 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13,592,454 patients across 31 studies underwent CRC screening using either gFOBT or FIT. Seventeen studies (3,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) reported on outcomes in patients using gFOBT and 14 studies (39,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) reported on FIT. Overall, 771,730 colonoscopies were performed in patients with an abnormal FIT (571,971) or positive gFOBT (199,759).…”
Section: Resultsmentioning
confidence: 99%
“…22 Adverse events of colonoscopy were significantly more frequent in our FIT CRC screening programme than usually estimated. 33 Accreditation for CRC screening could be seen as equivalent to double reading of mammograms for breast cancer screening; that is, as a way to offer the best possible chances to screened individuals.…”
Section: Discussionmentioning
confidence: 99%